Intralesional PV‐10 for the treatment of in‐transit melanoma metastases—Results of a prospective, non‐randomized, single center study. Issue 4 (12th March 2018) - Read, Tavis A.; Smith, Aaron; Thomas, Janine; David, Michael; Foote, Matthew; Wagels, Michael; Barbour, Andrew; Smithers, B. Mark
Abstract : Background: Patients with in‐transit melanoma metastases frequently experience high rates of recurrence, limited overall survival and reduced quality of life. After promising results within a Phase II, multi‐center study, PV‐10 treatment was continued at our institution for patients with in‐transit disease. Methodology: An open‐label, non‐randomized, prospective study was performed at the Princess Alexandra Hospital, Queensland, Australia. Patients were treated with PV‐10 in accordance with the treatment protocol established during a previous Phase II study. The primary outcome was the complete response of treated lesions. Results: Forty‐five patients were enrolled over a total of 82 treatment episodes from July 2008 to December 2015. With sequential PV‐10 treatments the complete response rate was 42% and overall response rate 87% on an intention to treat analysis. The median follow‐up duration was 22 months and the median overall survival was 25 months from first PV‐10 treatment. Having fewer than 15 metastases at the time of treatment was associated with a complete response ( P  = 0.03). Conclusions: Intralesional PV‐10 provided rapid lesion‐specific ablation of melanoma metastases with well‐tolerated local effects and minimal systemic adverse events. This therapy should be considered for patients with multiple accessible deposits within the spectrum of low to moderate disease volume.